1929
DOI: 10.1002/zaac.19291810133
|View full text |Cite
|
Sign up to set email alerts
|

Die Oberflächenspannung geschmolzener Metalle und Legierungen Die Oberflächenspannung von Gold, Zink, Gold‐Kupfer‐, Silber‐Kupfer‐ und Eisenlegierungen

Abstract: Es wurden die Oberflächenspannungen von Gold, Silber, Gold‐ Kupfer‐, Silber‐Kupferlegierungen nach der früher angewendeten Blasendruckmethode und diejenige von Zink und Legierungen von Eisen mit Kohlenstoff, Phosphor und Silicium nach etwas modifiziertem Verfahren bestimmt. Bemerkenswert ist die hohe Oberflächenspannung der Edelmetalle und ihrer Legierungen, sowie die hohe Oberflächenspannung der Eisenlegierungen und der teilweise positive Temperaturkoeffizient dieser Legierungen; bei einem Teil der Edelmetall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1932
1932
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The surface tension increases with increasing content of Cu; however, it is accompanied with a decrease in the surface tension temperature coefficient. In general, our data are in good agreement with the results of other authors [6,[8][9][10][11][12]. Most of the literature data were obtained with the SD, and only the data of Krause et al [9] were obtained with the MBP.…”
Section: Surface Tensionsupporting
confidence: 95%
See 2 more Smart Citations
“…The surface tension increases with increasing content of Cu; however, it is accompanied with a decrease in the surface tension temperature coefficient. In general, our data are in good agreement with the results of other authors [6,[8][9][10][11][12]. Most of the literature data were obtained with the SD, and only the data of Krause et al [9] were obtained with the MBP.…”
Section: Surface Tensionsupporting
confidence: 95%
“…In general, our data are in good agreement with the results of other authors [6,[8][9][10][11][12]. Most of the literature data were obtained with the SD, and only the data of Krause et al [9] were obtained with the MBP. For alloys of high Cu content, as well as pure Cu, the data of Krause et al [9] show a positive temperature coefficient, which is in contradiction to the data of other authors.…”
Section: Surface Tensionsupporting
confidence: 95%
See 1 more Smart Citation
“…Solid circles and open circles are measurements of the present work using the constrained drop and the traditional sessile drop methods, respectively. Both data are within the scatter of reported values (solid lines 9,[27][28][29][30][31][32][33][34][35][36][37] in Fig. 8: Every data referred in this contribution (Figs.…”
Section: Surface Tension Of Liquid Agsupporting
confidence: 81%
“…1, reported measurements are also drawn for comparison. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30] Keene 30) asserted in his review that the surface tension of liquid metal measured using the sessile drop method could be lowly estimated due to the contamination from the substrates (mainly oxides), and the surface tension measured by the levitation method usually showed higher surface tension values than that by the sessile drop method because the sample in the levitation method might not be contaminated from the substrate. However, Egry et al 29) showed that the surface tension of liquid metal droplets measured by the levitation method had been highly estimated due to the electromagnetic pressure on the liquid metal.…”
Section: Surface Tension Of Pure Liquid Ag Cu and Snmentioning
confidence: 99%